2019
DOI: 10.1016/j.crfs.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant active packaging systems to extend the shelf life of sliced cooked ham

Abstract: The effectiveness of active packaging systems with green tea extract and oregano essential oil was checked for their use in sliced cooked ham. Three packaging systems were evaluated: i) control group without active film, ii) ATGT packed with active film of green tea extract (1%) and iii) ATRX with a mixture of green tea extract and oregano essential oil (1%). The evolution of microbiological, physicochemical (pH, aw, colour and lipid oxidation) and sensory attributes were analysed after 0, 7, 14 and 21 days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 33 publications
(64 reference statements)
1
27
0
Order By: Relevance
“…Nevertheless, not only are organoleptic changes important during the development of lipid oxidation, but also the formation of toxic compounds such as aldehydes and the loss of nutritional values [ 5 ]. In this context, current tendencies in active packaging include the addition of active natural agents (such as essential oils or polyphenol-rich extracts) into the polymeric packaging materials, restricting the utilization of synthetic additives and extending the shelf life through a controlled release of these active substances into the food [ 6 , 7 , 8 , 9 ]. The use of polymer-based packaging for food products shows many benefits compared to other materials used in packaging applications, such as paper, aluminum or glass, since plastic materials are more flexible in terms of reducing weight and energy requirements for their production [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, not only are organoleptic changes important during the development of lipid oxidation, but also the formation of toxic compounds such as aldehydes and the loss of nutritional values [ 5 ]. In this context, current tendencies in active packaging include the addition of active natural agents (such as essential oils or polyphenol-rich extracts) into the polymeric packaging materials, restricting the utilization of synthetic additives and extending the shelf life through a controlled release of these active substances into the food [ 6 , 7 , 8 , 9 ]. The use of polymer-based packaging for food products shows many benefits compared to other materials used in packaging applications, such as paper, aluminum or glass, since plastic materials are more flexible in terms of reducing weight and energy requirements for their production [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results were very similar to those described by Jo et al [ 33 ], who reported that the vacuum-packed samples showed very low and stable oxidation values during storage, not observing differences between the pork sausages reformulated with chitosan and the controls, as well as during the 3-week storage period. Similarly, in a recent study conducted in cooked ham packaged with anaerobic modified atmosphere (70% N 2 /30% CO 2 ), the authors also found insignificant oxidation values [ 50 ] during 21 days of storage. These authors concluded that both the low fat content of cooked ham and the absence of O 2 were the two crucial factors for maintaining the lipid oxidation in insignificant values.…”
Section: Resultsmentioning
confidence: 75%
“…Increasing the safety of RTE products like sausages could be achieved using antimicrobial packaging [ 10 , 11 , 12 , 13 , 14 ]. Using natural antimicrobial compounds in packaging structures displays higher efficacy in comparison to direct use in the food matrix as an ingredient.…”
Section: Introductionmentioning
confidence: 99%